Optimizing Repayment Strategies for Egyptian Construction Companies with Multiple Loans - Elkady, Moataz (AUC Knowledge Fountain, 2023)
Optimizing Repayment Strategies for Egyptian Construction Companies with Multiple Loans is of utmost importance to efficiently allocate monthly income for loan repayment. The conventional practice of paying the minimum balance due each month leads to increased interest charges and prolonged repayment periods. In response, this research proposes a model for multiple loan repayment that considers the computational complexity involved. The model is built on the foundation of mixed integer linear programming and aims to establish an optimal repayment schedule by minimizing the total cash required to repay the loans, prioritizing the repayment of loans before personal expenses. The implementation of the model utilizes Mathematica software and the Gurobi optimizer. Through simulated cases using real data, the effectiveness of the proposed methodology is demonstrated. Debtors achieve average savings exceeding 12%, resulting in substantial reductions in payments made to banks or leasing companies. In certain scenarios, savings of up to 23.87% are attainable. The model takes into account debtors' revenue, expenses, as well as the associated interest rates, terms, and fees for each loan. This research challenges the prevailing debt repayment practices in construction companies by introducing an efficient and practical model for addressing the multiple loan repayment problem. By adopting the proposed model, construction companies gain the ability to make informed decisions regarding their financial circumstances and repayment strategies, ultimately leading to significant cost savings and enhanced financial stability. It is recommended to utilize the model to implement an optimized payment plan that considers the unique financial situation and cash flow projections of each construction company. Regular monitoring of loan repayment performance and necessary adjustments to optimize repayment strategies are crucial for sustained effectiveness. The proposed model presents construction companies with a powerful tool to optimize their repayment policies for multiple loans. Its adoption enables informed decision-making, resulting in notable cost savings and improved financial stability. This research makes a valuable contribution to the field of construction finance, potentially revolutionizing the approach to debt repayment within the industry.